P358 Ustekinumab is effective for the treatment of chronic antibiotic-refractory pouchitis. (25th January 2019) - Ollech, J E; Glick, L; Weisshof, R; Israel, A; El Jurdi, K; Krugliak Cleveland, N; Cohen, R D; Dalal, S R; Rubin, D T
Abstract: Background: Many ulcerative colitis (UC) patients develop pouchitis after proctocolectomy with ileal pouch-anal anastomosis (IPAA). Antibiotics have been the treatment of choice for pouchitis, but up to 15% of patients develop refractory disease. Ustekinumab (UST) is effective for the treatment of moderate-to-severe Crohn's disease and has recently been shown to be effective in UC. The aim of this study was to investigate the effectiveness of UST in the treatment of chronic antibiotic-refractory pouchitis. Methods: This is a retrospective tertiary centre study of patients evaluated between 2016–2018. Included were UC patients who had a total proctocoletomy with IPAA and who subsequently developed chronic antibiotic-refractory pouchitis and were treated with UST with standard Crohn's disease dosing. Patient demographic, clinical and endoscopic data were collected. All pouchoscopies were reviewed based on the endoscopy report and the images obtained. Outcomes of interest included change in the endoscopic subscore of the endoscopic Pouchitis Disease Activity Index (PDAI), change in the ulcerated surface area, clinical response, and number of bowel movements (BM). Results: We identified 24 UC patients with antibiotic-refractory pouchitis and who received UST. Median time from the start of UST treatment to pouchoscopy was 7.4 months IQR (4.6–10.6). Median follow-up time was 12.9 months IQR (7.9–16). Thirteen patients had pouchoscopies available post-UST treatment. The mean endoscopic subscore of the PDAI decreased from 4.8 to 3.3 ( p = 0.0076) post treatment (Figure 1). Before the start of UST therapy, 26.6% of patients had an ulcerated surface area >30%, this decreased to 8.3% after treatment with UST (Figure 2). Twelve patients (50%) achieved a clinical response and a reduction in mean bowel movements within 24 h from 8.4 to 6.5 ( p = 0.006) (Figure 3). Conclusions: In the largest single-centre study of UST treatment for patients with chronic antibiotic-refractory pouchitis, we found that UST therapy led to improvement in clinical and endoscopic endpoints. A prospective study is warranted.